2010
DOI: 10.1111/j.1365-2966.2010.16297.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field regulated infall on the disc around the massive protostar Cepheus A HW2

Abstract: We present polarization observations of the 6.7-GHz methanol masers around the massive protostar Cepheus A HW2 and its associated disc. The data were taken with the Multi-Element Radio Linked Interferometer Network. The maser polarization is used to determine the full three-dimensional magnetic field structure around Cepheus A HW2. The observations suggest that the masers probe the large scale magnetic field and not isolated pockets of a compressed field. We find that the magnetic field is predominantly aligne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
147
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(167 citation statements)
references
References 46 publications
(72 reference statements)
18
147
2
Order By: Relevance
“…The angle θ is likely to be similar for both transitions. Although not much is known about the decay rate of the masers (Vlemmings et al 2010), in our case, R is also similar for both maser transitions. The stimulated emission rate R is Note.…”
Section: Comparison Of Polarization Properties At 44 and 95 Ghzmentioning
confidence: 73%
See 1 more Smart Citation
“…The angle θ is likely to be similar for both transitions. Although not much is known about the decay rate of the masers (Vlemmings et al 2010), in our case, R is also similar for both maser transitions. The stimulated emission rate R is Note.…”
Section: Comparison Of Polarization Properties At 44 and 95 Ghzmentioning
confidence: 73%
“…For a long time, masers were thought to trace the isolated pockets of a compressed field rather than the field of an ambient medium. However, some recent studies of 1.6 GHz hydroxyl and 6.7 GHz methanol masers showed that they possibly probe the large-scale magnetic field (e.g., Fish & Reid 2006;Vlemmings et al 2010;Surcis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We made use of the adapted full radiative transfer method (FRTM) code for 6.7-GHz CH 3 OH masers (Vlemmings et al 2010;Surcis et al 2011b; to model the total intensity and the linearly polarized spectrum of every maser feature for which we were able to detect linearly polarized emission.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 6.7-GHz CH 3 OH masers, which are among the most abundant maser species in massive star-forming regions, are playing a crucial role in determining the magnetic field morphology (e.g., Surcis et al 2009Surcis et al , 2011bSurcis et al , 2012. Magnetic fields have mainly been detected along outflows and in a few cases on surfaces of disk/tori (Vlemmings et al 2010;Surcis et al 2009Surcis et al , 2011bSurcis et al , 2012. Moreover, 6.7-GHz CH 3 OH masers are also ideal for measuring the Zeeman-splitting even though the exact proportionality between the measured splitting and the magnetic field strength is still uncertain (Vlemmings et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation